Strategies of English Teachers’ Interpersonal Communication to Improve Students’ Speaking Skills at MTs Unggulan Al-Kautsar - Faiqotul Isma Dwi Utami (JETS: Journal of English Teaching Strategies, 2024)
The increasing role of English as a global lingua franca highlights the importance of speaking competence in English as a Foreign Language (EFL) classrooms. However, many students still experience anxiety, low confidence, and limited opportunities to practice speaking. This study investigates the interpersonal communication strategies used by an English teacher to improve students’ speaking skills at MTs Unggulan Al-Kautsar. Using a qualitative case study design, data were collected through classroom observations, semi-structured interviews, questionnaires, and documentation. The findings show that the teacher applied key interpersonal communication strategies, including teacher immediacy, supportive feedback, emotional encouragement, and open-ended questioning. These strategies created a supportive classroom atmosphere that reduced speaking anxiety and increased students’ confidence and participation. Questionnaire results indicated improvements in students’ willingness to communicate and engagement in speaking activities. The study confirms that interpersonal communication plays a crucial role in building a psychologically safe learning environment and enhancing speaking competence. This research contributes to instructional communication and EFL pedagogy by providing evidence from an Islamic junior high school context and suggests that integrating interpersonal communication strategies into speaking instruction can effectively improve students’ motivation, interaction, and communicative ability.